Investigating the substrate selectivity and the inhibitor of the human KDM7 sub-family of JmjC histone lysine demethylases - Zhang, Y (2019)
The regulation of gene expression by the post-translational modifications (PTMs) of histone tails is important in eukaryotic cell biology and of current medical interest. Specific PTMs to histone tails, including acetylation, phosphorylation and methylation, can either promote or inhibit transcription of specific sets of genes. Histone methylation was once thought to be irreversible but is no known to be dynamic. The extent of Ne-methyl lysine- and arginine-methylation is regulated by sets of methyl transferases and demethylases. The work described in this Thesis focused on the substrate selectivity and inhibition of the human KDM7 subfamily of JmjC histone demethylases (KDMs). KIAA1718 (KDM7A), PHF8 (KDM7B) have been demonstrated to be KDMs while PHF2 (KDM7C) is a proposed pseudo-enzyme. The KDM7 enzymes are part of the large family of JmjC KDMs which are 2-oxoglutarate (2OG) dependent oxygenases and which use Fe(II) as a cofactor. Most JmjC KDMs are multidomain proteins with the catalytic activity lying in their JmjC domain. However, other domains may regulate demethylation. The KDM7 enzymes are of particular interest because of their interesting demethylation activities and relatively simple domain architectures. Their plant homeodomains (PHDs) are proposed to bind to the histone H3K4me3 mark and in doing so either promote (PHF8), or inhibit (KIAA1718), demethylation by the JmjC domain of H3K9me2. Following an introduction to the epigenetic roles of KDMs (Chapter 1), Chapter 2 describes work on the kinetics of the KDM7 enzymes. Consistent with prior reports. PHF8 was found to demethylate H3K9me2 and its activity is enhanced by the presence of H3K4me3. KIAA1718 is reported to demethylate H3K9me2 and H3K27me2, the demethylation of which was either inhibited (H3K9me2) or enhanced (H3K27me2) by the binding of H3K4me3 mark. However, my results raise questions about the effect of H3K4me3 on demethylation of H3K27me2 by KIAA1718. New potential histone substrates were identified and characterised for both PHF8 and KIAA1718. Mechanistic studies were performed in Chapter 3 to investigate factors regulating KDM7 substrate binding. Mutagenesis studies and metal ion binding studies of wild-type and variant PHF8/PHF2 proteins revealed that although the HxD…H iron binding motif is crucial, other factors are involved in regulate the KDM activities of the KDM7 subfamily. The overall results reveal the PHD fingers are of primary importance in substrate binding. Using AlphaScreen and fluorescence polarisation methods, novel inhibitors for the KDM7 enzymes were investigated along with the mode of inhibition. In one line of investigation, a cyclic peptide inhibitor was identified to selectively inhibit the KDM activity of PHF8 and promote the activity of KIAA1718 at the H3K9me2 mark. Overall, the work described in this Thesis is supportive of the proposal that the PHD fingers of the KDM7 enzymes regulate their demethylation activities. Indeed, binding to the H3K4me3 mark by their PHD fingers appears to dominates substrate binding by the KDM7 enzymes. Blocking the binding of the PHDs of KDM7s can inhibit (PHF8) or promote (KIAA1718) demethylation activity.